ChemInform Abstract: Pd‐Catalyzed Three‐Component Reaction of 3‐(Pinacolatoboryl)ally Acetates, Aldehydes, and Organoboranes: A New Entry to Stereoselective Synthesis of (Z)‐anti‐Homoallylic Alcohols. Issue 43 (October 2015) - Horino, Yoshikazu; Aimono, Ataru; Abe, Hitoshi
Abstract The reaction does not proceed with tricyclohexyl‐ or tri‐s‐butylborane.